Effect of etch-and-rinse and self-etching adhesive systems on hardness uniformity of resin cements after glass fiber post cementation - da Cruz, Fernanda Zander Grande; Grande, Christiana Zander; Roderjan, Douglas Augusto; Arrais, César Augusto Galvão; Samra, Adriana Postiglione Bührer; Calixto, Abraham Lincoln (European Journal of Dentistry, 2012)
Objectives: To evaluate the effects of etch-and-rinse and self-etching adhesive systems on Vickers hardness (VHN) uniformity of dual-cured resin cements after fiber post cementation.Methods: Fifty glass fiber posts were cemented into bovine roots using the following cementing systems: Prime&Bond 2.1 Dual Cure and Enforce with light-activation (PBDC-LCEN); Prime&Bond 2.1 and Enforce with light-activation (PB-CLEN); Prime&Bond 2.1 Dual Cure and Enforce without light exposure (PBDC-SCEN); ED Primer and Panavia 21 (ED-SCPN); and Clearfil SE Bond and Panavia 21 (CF-SCPN). The roots were stored in distilled water for 72 h and transversely sectioned into thirds (coronal, medium, and apical). The VHN values of the resin cement layers were measured close to the post and to the dentin wall on the transversely sectioned flat surfaces. The results were analyzed by three-way repeated measures analysis of variance (ANOVA) and Tukey’s post-hoc test (pre-set alpha of 5%).Results: Most resin cements presented higher VHN values near the post than near the dentin wall. The ED-SCPN group showed the highest VHN values regardless of the root third, while the selfcured group PBDC-SCEN exhibited the lowest values. The resin cements from the light-activated groups PBDC-LCEN and PB-LCEN showed lower VHN values at the apical third than at the coronal third. The VHN values were not influenced by the root third in self-cured groups PBDC-SCEN, EDSCPN, and ED-SCPN.Conclusions: Depending on the product, bonding agents might promote changes in hardness uniformity of resin cements after post cementation. (Eur J Dent 2012;6:248-254)
Keywords: Resin cements; microhardness; fiber-glass posts